Headache characteristics in subarachnoid haemorrhage and benign thunderclap headache - Linn, F (BMJ Group, 1998)
One third of patients with aneurysmal subarachnoid haemorrhage (ASAH) present with headache only. A prompt diagnosis is crucial, but these patients must be distinguished from patients with non-haemorrhagic benign thunderclap headache (BTH). The headache characteristics and associated features at onset in subarachnoid haemorrhage and benign thunderclap headache were studied to delineate the range of early features in these conditions. In this prospective study, one of two observers interviewed 102 patients with acute severe headache by means of a standard questionnaire. The patients were alert on admission and had no focal deficits. ASAH was subsequently diagnosed in 42 patients, non-aneurysmal perimesencephalic haemorrhage (PMH) in 23 patients, and BTH in 37 patients. Headache developed almost instantaneously in 50% of patients with ASAH, 35% of patients with PMH, and 68% of patients with BTH and within 1 to 5 minutes in 19%, 35%, and 19%, respectively. Loss of consciousness was reported in 26% of patients with ASAH, 4% of patients with PMH and 16% of patients with BTH, and transient focal symptoms in 33%, 9%, and 22% respectively. Seizures and double vision had occurred only in ASAH. Vomiting and physical exertion preceding the onset of headache were more frequent in patients with ASAH (69% and 50%) and those with PMH (83% and 39%) than in those with BTH (43% and 22%). Headache developed almost instantaneously in only half the patients with aneurysmal rupture and in two thirds of patients with benign thunderclap headache. In patients with acute severe headache, female sex, the presence of seizures, a history of loss of consciousness or focal symptoms, vomiting, or exertion increases the probability of ASAH, but these characteristics are of limited value in distinguishing ASAH from BTH. Aneurysmal rupture should be considered even if focal signs are absent and the headache starts within minutes.